ACTR-21. A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED PHASE 3 TRIAL OF DEPATUXIZUMAB MAFODOTIN (ABT-414) IN EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) AMPLIFIED (AMP) NEWLY DIAGNOSED GLIOBLASTOMA (nGBM). (11th November 2019) - Lassman, Andrew; Pugh, Stephanie; Wang, Tony; Aldape, Kenneth; Gan, Hui; Preusser, Matthias; Vogelbaum, Michael; Sulman, Erik; Won, Minhee; Zhang, Peixin; Moazami, Golnaz; Macsai, Marian; et al.
Abstract: BACKGROUND: Approximately 50% of nGBMs harbor EGFR -amp. Depatuxizumab mafodotin (depatux-m) is an antibody drug conjugate: a monoclonal antibody that binds activated EGFR (wild-type and EGFRvIII mutant) linked to a microtubule-inhibitor toxin. Pre-clinical and earlier clinical trials suggested efficacy. METHODS: RTOGF 3508/AbbVie M13-813 (INTELLANCE-1, NCT02573324) was a phase 3 academic-industry collaboration (RTOG-Foundation, AbbVie). Eligible adults (KPS ≥ 70, EGFR -amp nGBM, centrally confirmed histology and biomarkers) were randomized 1:1 to radiotherapy (RT) and temozolomide and either depatux-m (2.0 mg/kg during RT, 1.25 mg/kg thereafter, q 14 days) or placebo, stratified by region of world, RPA class, MGMT methylation, and EGFRvIII mutation. Primary endpoint was overall survival (OS), with 640 patients planned for randomization; 441 events yielded 85% power to detect 25% reduction in hazard of death (HR 0.75), one-sided 2.5% level of significance by stratified weighted log-rank. RESULTS: 2229 patients were screened and 639 (median age 60, range 22–84; 394 men, 62%) randomized. Pre-specified interim analysis after 346 events (≥ 75% required) found no OS improvement for depatux-m over placebo (median 18.9 vs. 18.7 months, HR 1.01, 95% CI 0.82–1.25, one-sided p= 0.63). Progression-free survival (PFS) trended toward depatux-m (median 8.0 vs. 6.3 months; HR 0.84, 95% CI 0.70–1.02), particularly among the ~50% with EGFRvIII mutation (median 8.3 vs. 5.9 months, HR 0.72, 95% CI 0.56–0.93) but without an OS improvement (median 19.8 vs. 18.2, HR=0.95, 95% CI 0.71–1.27). Ocular side effects (grade ≥ 1) occurred in 95% of depatux-m treated patients, 61% grade 3–4, causing 12% to discontinue, and were the most common treatment related adverse events. CONCLUSION: Interim analysis demonstrated no OS benefit for treating EGFR -amp nGBM with depatux-m. PFS trended toward favoring depatux-m, particularly in the EGFRvIII harboring subgroup. No new important safety risks were identified. The trial was stopped for futility. Active patients are permitted to continue treatment.